STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL STUDY OF GROUNDWATER IN HYDROCHEMICAL - Z, . Benkhamallah; M, Benyahia ,; 1, Ayache A (university of eloued جامعة الوادي, 2020)
Groundwater resources are Groundwater resources are Groundwater resources are Groundwater resources are Groundwater resources are Groundwater resources are Groundwater resources areGroundwater resources areGroundwater resources are Groundwater resources areGroundwater resources are very sc very sc very sc arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological arce in the Ain Temouchent region due to geological nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs nature. Their operations are essential to increase the volume of water meet needs population, socio population, socio population, socio -economic economic economic economic economic economic development; development; development; development;development; agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the agriculture and urbanization have accentuated the proble m of the m of the m of them of the ir shortages ir shortages ir shortages ir shortages ir shortages. The results of the physico The results of the physicoThe results of the physico The results of the physico The results of the physico The results of the physicoThe results of the physico The results of the physico The results of the physicoThe results of the physico The results of the physicoThe results of the physico-chemical chemical chemical chemical chemical chemical chemical analyzesanalyzes analyzes analyzesanalyzesanalyzes of the various of the various of the various of the various of the various of the various of the various samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, samples taken from the fifteen underground sources; show us that these waters are chlorinated, sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, an sulphated, calcic and magnesian in nature; Bicarbonate, ansulphated, calcic and magnesian in nature; Bicarbonate, sodic d sodic d sodic d sodic and and and potassic, wi th high electrical conductivity th high electrical conductivity th high electrical conductivityth high electrical conductivity th high electrical conductivity th high electrical conductivity th high electrical conductivity th high electrical conductivityth high electrical conductivity th high electrical conductivity th high electrical conductivity th high electrical conductivity and significant mineralizationand significant mineralization and significant mineralization and significant mineralization and significant mineralizationand significant mineralization and significant mineralization and significant mineralization and significant mineralization and significant mineralization and significant mineralizationand significant mineralizationand significant mineralization and significant mineralization , evolve slightly from , evolve slightly from , evolve slightly from , evolve slightly from , evolve slightly from , evolve slightly from , evolve slightly from , evolve slightly from , evolve slightly from south to north. south to north. south to north. south to north. A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are A predominance of chlorides, magnesium, a high content calcium, are influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy ofinfluenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy ofinfluenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy ofinfluenced in some places by the lithology and mineralogy ofinfluenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of influenced in some places by the lithology and mineralogy of the aqu the aquthe aqu ifer, but also by ifer, but also by ifer, but also by ifer, but also by ifer, but also by ifer, but also by ifer, but also by precipitation and high evaporation in these areas, some cases by the overexploitation of precipitation and high evaporation in these areas, some cases by the overexploitation of precipitation and high evaporation in these areas, some cases by the overexploitation of
artical
Keywords: Aïn T Aïn Temouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature.mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature.mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature. mouchent, groundwater, quality, hydrochemistry, geological nature.mouchent, groundwater, quality, hydrochemistry, geological nature.mouchent,